2020
DOI: 10.1136/bmjdrc-2019-000980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the low carbohydrate, high fat diet on glycemic control and body weight in patients with type 2 diabetes: experience from a community-based cohort

Abstract: ObjectiveThe optimal diet to improve glycemia in patients with type 2 diabetes remains unclear. Low carbohydrate, high fat (LCHF) diets can improve glycemic control, but have not been investigated in real-world settings.Research design and methodsWe investigated effects of the LCHF diet compared with usual care in a community-based cohort of patients with type 2 diabetes by performing a retrospective study of 49 patients who followed the LCHF diet for ≥3 months, and compared glycemic outcomes with age-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
2
16
0
2
Order By: Relevance
“…In a RCT by Retterstol et al, a low carbohydrate diet coupled with high dietary fat intake has been found to increase plasma LDL-C by 44% (range between 5% and 107%) compared to the control group in normal weight individuals over a period of 3 weeks [ 86 ], which could increase CVD risk. However, studies on the metabolic effects of low carbohydrate high fat diets, namely on lipid profile, report inconsistent findings and while some do not note any differential impact, others indicate improvements in lipid markers among a range of other metabolic benefits including greater reductions in HbA1C and better glycemic control in patients with type 2 diabetes [ 87 , 88 , 89 ]. A low intake of carbohydrates, namely dietary fibers, is also known to be associated with negative effects on the gut function and overall health [ 90 , 91 ].…”
Section: Dietary Interventions In the Management Of Obesitymentioning
confidence: 99%
“…In a RCT by Retterstol et al, a low carbohydrate diet coupled with high dietary fat intake has been found to increase plasma LDL-C by 44% (range between 5% and 107%) compared to the control group in normal weight individuals over a period of 3 weeks [ 86 ], which could increase CVD risk. However, studies on the metabolic effects of low carbohydrate high fat diets, namely on lipid profile, report inconsistent findings and while some do not note any differential impact, others indicate improvements in lipid markers among a range of other metabolic benefits including greater reductions in HbA1C and better glycemic control in patients with type 2 diabetes [ 87 , 88 , 89 ]. A low intake of carbohydrates, namely dietary fibers, is also known to be associated with negative effects on the gut function and overall health [ 90 , 91 ].…”
Section: Dietary Interventions In the Management Of Obesitymentioning
confidence: 99%
“…27 28 This approach has been reported with similar results in another center. 29 ► Eight who engaged with the Unwin diet experienced a reduction in weight from 110.2±19 to 101.5±20 kg and of HbA1c from 52.8±7 to 45.2±3.4 mmol/mol, at 1 year, p=0.00003 for both weight loss and reduction in HbA1c.…”
Section: Single Practice Interventionmentioning
confidence: 96%
“…The reduction of carbohydrate intake naturally reduces blood glucose levels, thus reducing insulin as a result. Many studies have now demonstrated that the ketogenic diet reduces both blood glucose and insulin levels [ 55 , 56 , 57 ]…”
Section: The Effect Of the Ketogenic Diet On Weight Lossmentioning
confidence: 99%